Acridocarpus smeathmannii root extracts inhibit human prostate and bladder smooth muscle contraction, porcine arterial vasoconstriction, and cytotoxicity of prostate stromal cells - Kale, Oluwafemi Ezekiel; Hu, Sheng; Huber, Claudia; Schierholz, Felix; Ciotkowska, Anna; Tamalunas, Alexander; Stief, Christian G.; Eisenreich, Wolfgang; Hennenberg, Martin (Frontiers in Pharmacology, 2025)
IntroductionThe limited tolerability and efficacy of synthetic drugs have hindered the effective management of lower urinary tract symptoms (LUTSs). In African traditional medicine, species of the genus Acridocarpus (Malpighiaceae) are commonly used to treat reproductive disorders. In this study, we investigated the bioactivity-guided effects of Acridocarpus smeathmannii on smooth muscle contractility using human tissues obtained from radical prostatectomy and cystectomy procedures, as well as porcine coronary and interlobar arteries. Additionally, the impact of A. smeathmannii on the proliferation of cultured prostate stromal cells was evaluated.MethodsCumulative concentration–response curves were generated for both adrenergic and cholinergic agonists, and electrical field stimulation (EFS) in organ bath experiments. In addition, assays were conducted to evaluate cell proliferation and viability, providing complementary insights into functional and cellular-level effects. The bioactive compounds in the extract were characterized using gas chromatography–mass spectrometry (GC-MS) and nuclear magnetic resonance spectroscopy and were subsequently evaluated in silico for their interaction with the α1-adrenergic receptor.ResultsProstate tissue contractions induced by α1-adrenergic agonists (0.1–100 µM) were reduced by 50% or more with A. smeathmannii at concentrations of 0.25 and 0.50 mg/mL. Bladder tissue contractions induced by the cholinergic agonists (0.1–1000 µM) were reduced by over two-thirds. Neurogenic contractions induced by EFS (2–32 Hz) were inhibited by up to 90% in both prostate and bladder tissues. Similarly, A. smeathmannii moderately inhibited contractile responses in porcine arteries. Moreover, A. smeathmannii inhibited the proliferation and viability of cultured prostate stromal cells in a concentration-dependent manner. In silico studies revealed that stigmasterol and pinostrobin chalcone showed the highest binding affinity to the α1-adrenergic receptor.ConclusionIn this study, we report for the first time that A. smeathmannii extract inhibits α1-adrenergic and cholinergic contractions in the prostate, bladder, and porcine arteries, with effects comparable to those of α1-blockers and anticholinergics. Additionally, in silico studies revealed that phytosterols, flavonoids, and benzoate esters in the extract exhibit supportive binding affinity to the α1-adrenergic receptor. Hence, A. smeathmannii may hold promise as a potential therapeutic agent for mixed-type LUTS.